Application of Storytelling Play Therapy to Reduce Pain Levels in Children with Leukemia - Rahayu, Rika Puji; Imamah, Ida Nur; Azizah, Lin Marhamah (KIAN JOURNAL, 2023)
Objective: The purpose of this study was to determine the effect of storytelling play therapy on reducing pain levels in children with leukemia in Flamboyant Room 9 at Dr. Moewardi Hospital Surakarta. Methods: The research method used is the descriptive method with a pre- and post-test in the intervention group with a case study design. Results: The results of this study indicate a decrease in pain levels in children with leukemia after being given storytelling play therapy for 3 consecutive days. Before the application of the pain scale, the two respondents experienced pain on a scale of 5 (moderate pain) and 4 (moderate pain), after being given the pain scale on scales 2 (mild pain) and 1 (mild pain). Conclusion: There is a decrease in the level of pain in children with leukemia after storytelling play therapy for 3 consecutive days at Dr. Moewardi Surakarta Hospital.